ReCal OIR: Ordinal, Interval, and Ratio Intercoder Reliability as a Web Service - Freelon, Deen (International journal of internet science, 2013)
This article introduces ReCal OIR, an extension to the existing ReCal suite of online intercoder reliability modules that accommodates ordinal, interval, and ratio levels of measurement. It includes a discussion of the currently available options for calculating reliability for the ordinal, interval, and ratio levels; explains what ReCal OIR does; validates its calculations; and discusses its usage data. The process of validating its output reveals ReCal OIR to be slightly more accurate than one of its major competitors. Adapted from the source document.